Drift diving: A quick and accurate method for assessment of anadromous salmonid spawning populations. (4th May 2021) - Skoglund, Helge; Vollset, Knut Wiik; Lennox, Robert; Skaala, Øystein; Barlaup, Bjørn Torgeir
Abstract: The accuracy of drift diving surveys of Atlantic salmon, Salmo salar L. and sea trout, Salmo trutta L., was evaluated by comparing the abundance and size distribution with catches in a fish trap over 6 years in the River Etneelva, western Norway. The population count from drift diving accounted for on average 96.3% of the salmon in the trap after accounting for the catches during fishing. Size structure registered during drift diving corresponded with trap catches of salmon, but the number of small salmon (<3 kg) appeared to be somewhat underestimated, while large salmon (>7 kg) were overestimated in drift diving. For sea trout, the match between drift diving counts and trap registrations was poorer (average 76.3%), but may have been affected by the surveys being performed too late with regards to sea trout spawning time. The study illustrates the utility of drift counting for estimating the entire population of anadromous salmonids in a river.